A study on profile and problem faced by cooperatives in West Coast of Sabah / Norazmah Abdul - Abdul, Norazmah (2006)
After done this research, we can see that, cooperatives is one of the business organization, and it is very important for the government to continuously support, observed, and investigate cooperatives business activity in order to avoid mismanagement and misconception about the cooperatives philosophy and principles. From this research we find out that, board of members had an internal and external problem in order to develop cooperatives business activities. Other than that, they also most prefer to attend any JPK program in order to solve the cooperatives problem. Meaning to say, JPK is an organization that has play a very important role in order to help, support and observed the cooperatives development. Through this research, the researcher has been discovering the profile of the cooperative such as its business activities, district and education of the board members and also the major problem that the cooperatives had faced and the related factor that had contribute to this problem. These relationships also help the researcher to achieve the objectives of this study.